Social inequalities and parent involvement in children's education in the early years of school. - Walker, S; Berthelsen, D (Nova Science Publishers, 2010)
Previous research has shown that parental involvement in their children’s schooling is associated with higher levels academic achievement and engagement in school by children. This chapter examines whether social and cultural capital and socioeconomic status affect levels of parental involvement. The chapter discusses some of the issues, and presents findings from Australian research comparing parent background and levels of parental involvement, as measured by teacher and parent reports. Data is taken from the Longitudinal Study of Australian Children, for primary-school aged children aged 6 to 7 years old. The study found that higher socioeconomic status was associated higher levels of involvement and higher academic expectations.
Delving into diversity: An international exploration of issues in diversity in education
Keywords: Education and Training; Learning, education and training; Education and Training; Learning, education and training